The role of gut microbiota alteration in rats fed a diabetogenic diet on the development of type 2 diabetes - Kuabayina, Anicet I.; Amogu, Jean-Jacques D.; Diazuangani, Didier; Makwela, Lyz N.; Katunda, Ruth M.; Kabena, Odette N. (Orapuh Journal, 2024)
Introduction Diabetes is a chronic metabolic disorder characterized by hyperglycemia, marked dyslipidemia, and pancreatic β-cell dysfunction. Despite numerous management measures for type 2 diabetes mellitus (T2DM), its incidence is not decreasing. Objective This study aimed to investigate the effects of gut dysbiosis induced by amoxicillin and a gut microbiota maintained by plant fiber on the prevention of T2DM development. Methods Sixteen Wistar rats purchased from INRB were subdivided into four groups. The intestinal microbiota of group 2 (G2) was altered by amoxicillin (AX), while that of group 4 (G4) was maintained by plant fibers. Intestinal dysbiosis was assessed using PCA culture and surface colony count. Glycemia and weight were assessed weekly, and insulin sensitivity was measured using the hyperglycemic glucose tolerance test (HGPO) after 8 weeks. Results AX reduced the baseline bacterial concentration by 99.99% (p = 0.039) after 2 weeks of treatment, but its action did not differ between males and females (p = 0.28). Weight gain did not differ between groups for either males (p = 0.24) or females (p = 0.50). Similarly, blood glucose levels did not differ between males (p = 0.87) and females (p = 0.06) in any of the groups. However, intestinal dysbiosis reduced the risk of diabetes in males of the G2 group but increased it in females of the same group. Conversely, the risk of T2DM was significantly reduced in both males and females in the G4 group. Conclusion Intestinal dysbiosis delays the onset of T2DM in males but increases the risk in females, while a well-maintained intestinal microbiota delays its onset in both sexes.